2020
DOI: 10.3357/amhp.5601.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of hs-CRP on Cardiovascular Risk Stratification in Pilots and Air Traffic Controllers

Abstract: INTRODUCTION: We assessed determinants of serum hs-CRP level in pilots and air traffic controllers (ATCs) and its impact on their atherosclerotic cardiovascular disease (ASCVD) risk.METHODS: We obtained serum hs-CRP measurements, evaluated traditional cardiovascular risk factors and assessed global ASCVD risk based on 2018 ESH/ESC guidelines. Elevated hs-CRP was hs-CRP values > 3 mg L1. Determinants of elevated hs-CRP were assessed using stepwise logistic regression analysis. We used the net reclassificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Moreover, the 2013 ACC/AHA guidelines on the assessment of CV risk recommend hs-PCR in men (>50 y) and in women (>60 y) at intermediate risk, which are qualified for lipid lowering drugs [39]. In this regard, many studies reported a robust association of hs-CRP with numerous traditional risk factors for CHD such as obesity, diabetes, physical inactivity, smoking, and alcohol use [40][41][42]. Other studies highlighted the modest relationship between hs-CRP and CVD, because of its variability among age, gender (higher magnitude in men), and ethnicity (higher magnitude in African Americans vs. Caucasians) [43,44].…”
Section: High Sensitivity C-reactive Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the 2013 ACC/AHA guidelines on the assessment of CV risk recommend hs-PCR in men (>50 y) and in women (>60 y) at intermediate risk, which are qualified for lipid lowering drugs [39]. In this regard, many studies reported a robust association of hs-CRP with numerous traditional risk factors for CHD such as obesity, diabetes, physical inactivity, smoking, and alcohol use [40][41][42]. Other studies highlighted the modest relationship between hs-CRP and CVD, because of its variability among age, gender (higher magnitude in men), and ethnicity (higher magnitude in African Americans vs. Caucasians) [43,44].…”
Section: High Sensitivity C-reactive Proteinmentioning
confidence: 99%
“…Other studies highlighted the modest relationship between hs-CRP and CVD, because of its variability among age, gender (higher magnitude in men), and ethnicity (higher magnitude in African Americans vs. Caucasians) [43,44]. A study comprised of aircrew from both African and Caucasian origin reported a net reclassified global ASCVD risk based on 2018 ESC/ESH guidelines chiefly in intermediate risk hypertensive individuals [40].…”
Section: High Sensitivity C-reactive Proteinmentioning
confidence: 99%